Review on Aspect Based Sentiment Analysis Using Sentence Minimization - Likhar, M; Kasar, SL (International Journal of Computer Sciences and Engineering, 2025)
The idea behind the sentiment analysis is to determine the sense trailing the response of product, present in a series of words. It assists us to determine the possible approach mention online. To achieve an idea present in the response of reviews, sentiment analysis is quite useful and defines the overview of public opinion behind the social media elements. Natural language is too complex for machine to follow. To instruct the machine regarding all the feelings, culture, slang and innovation are one of the major challenges for developer. Portray the system to realize the affect of tone is even more difficult. Natural language processing plays a vital role for categorizing the words as ‘positive’ or ‘negative, without having the knowledge regarding the context, it becomes very difficult to analyze the sentiment. In basic way feedback shows the better information about what exactly required, this helps to automate the system using natural language processing.